2008
DOI: 10.1186/1297-9686-40-1-61
|View full text |Cite
|
Sign up to set email alerts
|

Detection of quantitative trait loci for reproduction and production traits in Large White and French Landrace pig populations (Open Access publication)

Abstract: -A genome-wide scan was performed in Large White and French Landrace pig populations in order to identify QTL affecting reproduction and production traits. The experiment was based on a granddaughter design, including five Large White and three French Landrace half-sib families identified in the French porcine national database. A total of 239 animals (166 sons and 73 daughters of the eight male founders) distributed in eight families were genotyped for 144 microsatellite markers. The design included 51 262 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 37 publications
(35 reference statements)
2
24
1
2
Order By: Relevance
“…those located on SSC 6, 9 and 12, did not correspond to any previously described QTL. Conversely, the SSC 18 QTL detected using HFS model had the same location and rather similar effects (1.2 piglets born alive v. 1.37 embryos) as that recently detected in French Large White and Landrace pig populations (Tribout et al, 2008). The QTL detected on ES do not correspond to the single previously published QTL on prenatal survival (King et al, 2003).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…those located on SSC 6, 9 and 12, did not correspond to any previously described QTL. Conversely, the SSC 18 QTL detected using HFS model had the same location and rather similar effects (1.2 piglets born alive v. 1.37 embryos) as that recently detected in French Large White and Landrace pig populations (Tribout et al, 2008). The QTL detected on ES do not correspond to the single previously published QTL on prenatal survival (King et al, 2003).…”
Section: Discussionsupporting
confidence: 60%
“…Results for ovulation rate are slightly more numerous, as 14 chromosomal regions associated with variations in OR are reported in PiqQTLdb (Rohrer et al, 1999;Wilkie et al, 1999;Cassady et al, 2001;Campbell et al, 2003). Regarding litter size, 12 QTL located on 10 different chromosomes have been reported (Rathje et al, 1997;Cassady et al, 2001;de Koning et al, 2001;Noguera et al, 2006;Tribout et al, 2008), of which only those reported by Noguera et al (2006) reached a genome-wide significance level (P , 0.05).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, several QTL of the QTL regions identified in this study were found to carry reproduction QTL in other studies. For instance, the SSG6 QTL affecting the length of uterine horns was close to the QTL affecting litter size detected by Wilkie et al (1999), Tribout et al (2008), and Li et al (2009). The QTL affecting ovarian weight in the SW1354-SW1369 interval on SSG7 contains the properdin locus, which was shown to be associated with litter size at birth by Buske et al (2005).…”
Section: Discussionmentioning
confidence: 94%
“…When QTL are detected in such populations, they cannot be directly used in selection programmes and additional studies are required to confirm the existence of these QTL in commercial populations. Nevertheless, genome scans are carried out on an increasing -E-mail: marie-pierre.sanchez@jouy.inra.fr number of crosses of commercial populations: Yorkshire 3 Berkshire (Malek et al, 2001a and2001b), Piétrain 3 Large White (Nezer et al, 2002), Iberian 3 Landrace (Varona et al, 2002), Hampshire 3 Landrace (Karlskov-Mortensen et al, 2005) or Duroc 3 Piétrain populations (Liu et al, 2007;Edwards et al, 2008a and2008b) and even on purebred commercial populations (Evans et al, 2003;Vidal et al, 2005;Tribout et al, 2008). All these studies revealed a large number of QTL, suggesting that different alleles are fixed in distinct commercial populations or that QTL are still segregating in purebred populations after many generations of selection.…”
Section: Introductionmentioning
confidence: 99%